Peran Mediator dalam Proses Mediasi Upaya Menyelesaikan Perkara Perdata (Studi Kasus di Pengadilan Negeri Pasuruan) - Ristiana Dewi (Postgraduate University of Merdeka Malang, 2021)
The purpose of this study is to analyze the role of mediators in the me-diation process for efforts to settle civil cases and examine the obstacles faced by mediators in mediating efforts to resolve civil cases. This re-search is an empirical legal research because it identifies the role of mediator. The results show that the effectiveness of the mediator's role in the settlement of civil cases in the Pasuruan District Court has been running well. Mediators consisting of judges and substitute clerks can bridge, reconcile and mediate the problems of the two disputing parties. Based on data in the field, the obstacles that cause failures in the media-tion process are as follows: mediators are still not proactive in carrying out mediation tasks, among others; the disputing parties, outside medi-ators do not understand the mediation procedure in accordance with applicable regulations, there are often disagreements between the dis-puting parties because they focus on winning and losing alone, not a win-win solution for the common good. The mediator must really un-derstand his role as a mediator so that deadlocks or obstacles are not found in the mediation process.DOI: https://doi.org/10.26905/mlj.v2i1.6254